Study of structural, magnetic, magnetocaloric properties and critical behavior of CoFeCuO4 spinel ferrite - Nasri, M. (2021)
Our research work centers on studying the structural, magnetic, magnetocaloric properties and the critical behavior of the Cu-substituted CoFe2O4. The XRD analysis revealed that this compound prepared via sol-gel method crystallized in the cubic spinel structure with the Fd3m space group and exhibited nanometric size. In addition, the positive slope in Arrott plots and the universal master curve confirmed the second order ferromagnetic-paramagnetic (FM-PM) phase transition exhibited by our material at a Curie temperature TC = 688 K. Furthermore, it is demonstrated that substituting iron by copper in CoFe2O4 decreases the Curie-temperature and increases the maximum magnetic entropy change. Indeed, for CoFeCuO4, the magnetic entropy change (-Delta SM) rose upon increasing the applied magnetic field and presented a peak around the Curie temperature, its maximum value (-Delta SmaxM ) of 0.6 J.kg- 1.K-1 is reached at mu 0H = 5 T, it corresponds to a relative cooling power (RCP) value of 62.55 J.kg- 1. Moreover, the heat capacity Delta CP was evaluated in order to explore further the performance of our compound with respect to the magnetocaloric effect (MCE). As a final point, the critical exponents were estimated through different experimental and theoretical techniques, they are found reliable obeying to the mean-field model, symptomatic of short-range ferromagnetic interactions.